2015
DOI: 10.1111/1750-3841.12830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Germination on the Nutritional Properties, Phenolic Profiles, and Antioxidant Activities of Buckwheat

Abstract: Germination is considered to be an effective process for improving the nutritional quality and functionality of cereals. In this study, changes of nutritional ingredients, antinutritional components, chemical composition, and antioxidant activities of buckwheat seeds over 72 h of germination were investigated, and the reasons for these changes are discussed. With the prolonged germination time, the contents of crude protein, reducing sugar, total phenolics, total flavonoids, and condensed tannins increased sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
135
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 23 publications
14
135
3
Order By: Relevance
“…Phytochemicals are important plant secondary metabolic products produced in phenylpropanoid biosynthesis and shikimate pathways during the growth of plants (Zhang, Xu, Gao, Huang, & Yang, 2015). During growth, L‐phenylalanine, under the effect of phenylalanine ammonia lyase (PAL) catalyzation, changes into cinnamic acid.…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 99%
See 4 more Smart Citations
“…Phytochemicals are important plant secondary metabolic products produced in phenylpropanoid biosynthesis and shikimate pathways during the growth of plants (Zhang, Xu, Gao, Huang, & Yang, 2015). During growth, L‐phenylalanine, under the effect of phenylalanine ammonia lyase (PAL) catalyzation, changes into cinnamic acid.…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 99%
“…These can later be converted into tannins, flavonoids, lignins, and other compounds. Advances in research have revealed importance of these phytonutrients to human health by virtue of their antioxidant properties (Zhang et al., 2015), cholesterol‐lowering effect (Golzarand, Mirmiran, Bahadoran, Alamdari, & Azizi, 2014; Gunness & Gidley, 2010), and reduction in the production of pro‐inflammatory cytokines and immunosuppressive cells (Lesinski et al., 2015). Due to the complexity of studying phytochemicals, few studies have focused on studying the effects of traditional processing techniques due to limited capacity in most laboratory studying these traditional methods.…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 99%
See 3 more Smart Citations